ANALYSIS OF NURSING CARE FOR PREGNANT WOMEN WITH THE IMPLEMENTATION OF FE TABLET EDUCATION THROUGH METHOD AUDIOVISUALS TO OVERCOME THE DEFICIT KNOWLEDGE OF ANEMIA - Alistia, Sabila Rohmatul Ula (Nurse and Holistic Care, 2023)
Background: Anemia is a micronutrient problem in the form of a condition of deficient levels of hemoglobin (Hb) in the blood caused by low intake of iron which is needed for the formation of Hb. Not consuming Fe tablets in pregnant women is the most common cause of anemia in pregnant women. Objective: The aim is to analyze nursing care for pregnant women by implementing Fe tablet education through audiovisual methods to overcome anemia knowledge deficits. Methods: This research design uses descriptive in the form of a case study in the nature of nursing care including nursing assessment, nursing diagnosis, nursing intervention, nursing implementation and nursing evaluation. The research was carried out at the RSI Jemursari Surabaya. The time for taking this case study research was carried out by the researcher at January 10 to 12, 2023. Research was carried out for 3 days. Result: The results of the research after implementing Fe tablet education via audiovisual media on anemia in pregnant women 3 times in 3 days with an implementation time of 15 minutes showed that the patient's level of knowledge increased from scale 2 (moderately decreased) to scale 3 (moderate). Conclusion: The conclusions from the case study show that the application of Fe tablet education via audiovisual is effective as a nursing intervention for anemia problems in pregnant women.